Polysulfide rejection layer from alpha-lipoic acid for high performance lithium–sulfur battery. Issue 1 (14th November 2014) - Song, Jongchan; Noh, Hyungjun; Lee, Hongkyung; Lee, Je-Nam; Lee, Dong Jin; Lee, Yunju; Kim, Chul Hwan; Lee, Yong Min; Park, Jung-Ki; Kim, Hee-Tak
Abstract : Polysulfide shuttle of lithium–sulfur batteries can be suppressed by alpha-lipoic acid, an electrolyte additive, which forms a polysulfide rejection layer on sulfur cathode and a stable SEI layer on Li metal anode. Abstract : The polysulfide shuttle has been an impediment to the development of lithium–sulfur batteries with high capacity and cycling stability. Here, we report a new strategy to remedy the problem that uses alpha-lipoic acid (ALA) as an electrolyte additive to form a polysulfide rejection layer on the cathode surface via the electrochemical and chemical polymerization of ALA and a stable solid electrolyte interface (SEI) layer on the Li metal anode during the first discharge. The poly(ALA) layer formed in situ effectively prevents the polysulfide shuttle and consequently enhances the discharge capacity and cycling stability, owing to the Donnan potential developed between the polysulfide-concentrated cathode and the fixed negative charge-concentrated poly(ALA) layer. Also, the SEI layer additionally prevents the chemical reaction of the polysulfide and Li metal anode. The approach, based on the double effect, encompasses a new scientific strategy and provides a practical methodology for high performance lithium–sulfur batteries.